Subsidies and allocation: A legacy of distortion and intergenerational loss - Sinan, Hussain; Willis, Ciara; Swartz, Wilf; Sumaila, U. Rashid; Forsdyke, Ruth; Skerritt, Daniel J.; Le Manach, Frédéric; Colléter, Mathieu; Bailey, Megan (Frontiers in Human Dynamics, 2022)
One of the greatest threats to the management of transboundary stocks is the failure of Regional Fisheries Management Organizations (RFMOs) to allocate future fishing opportunities equitably. Across RFMOs, catch history remains the principal criterion for catch allocations, despite being recognized as a critical barrier to governance stability. This paper examines if and how subsidies have driven catch histories, thereby perpetuating the legacy of unfair resource competition between distant water fishing nations (DWFNs) and coastal States, and how this affects ongoing allocation negotiations in the Indian Ocean Tuna Commission (IOTC). Using limited publicly available data on subsidies to Indian Ocean tuna fleets, we show that subsidies have inflated the catch histories of many DWFNs. As long as historical catch remains the key allocation criterion, future fishing opportunities will continue to be skewed in favour of DWFNs, in turn marginalizing half of the IOTC member States, which collectively account for a paltry 4% of the current catch. Without better transparency in past subsidy data, accounting for this distortion will be difficult. We provide alternative allocation options for consideration, with our analysis showing that re-attributing DWFN catch to the coastal State in whose waters it was caught may begin to alleviate this historical injustice.